Risk factors of clinical deterioration in cerebral contusions - M. Ye. Polishchuk; M. B. Vyval; O. M. Honcharuk; A. B. Muravskyi; A. A. Oblyvach (Zaporozhye State Medical University, 2020)
Evaluation of the relationship between radiological progression of cerebral contusion and clinical course is the object of many recent studies. The aim of the study is to identify factors that are associated with clinical deterioration in patients with brain contusions. Materials and methods. The study included 148 patients with brain injuries, who were treated at the Kiev City Clinical Emergency Hospital in 2016-2017. Results. 43.9 % patients were in conscious or obtunded, 31.8 % were in stupor and 24.3 % in a coma. The average time to computed tomography was 4.3 ± 3.3 hours. Brain damage according to Marshall classification: type II - 60.8 %, type III - 26.4 %, IV - 8.8 %, type VI - 4.1 % patients, types I and V belonged to exclusion criteria. In the first 24 hours, clinical deterioration was found in 18.9 %, improvement in 16.2 % and stable neurological status in 64.8 % patients. Another 5.4 % patients worsened after the first day (on days 2-8). The cause of the clinical deterioration was the hemorrhagic progression of contusion, the increase of the epi-subdural hematoma, and brain edema. An analysis of treatment outcomes in patients with clinical deterioration revealed a higher risk of adverse outcome (1-3 points on the Glasgow outcome scale at discharge) compared to patients without clinical deterioration. Conclusions. Low Glasgow coma scale score at admission, the size of the contusion more than 25 ml, midline shift, basal cisterns compression and epidural hematoma were the risk factors of the clinical deterioration. The early determination of secondary hemorrhagic progression of contusion and clinical deterioration with modification of treatment strategy are important in improving the prognosis after traumatic brain injury.